Protective effect of Huangpu Tongqiao capsule against Alzheimer's disease through inhibiting the apoptosis pathway mediated by endoplasmic reticulum stress in vitro and in vivo - Xinquan Li; Yunpeng Qin; Shu Ye; Hang Song; Peng Zhou; Biao Cai; Yan Wang (Elsevier, 2022)
Objectives: Huangpu Tongqiao Capsule (HPTQC) is a traditional Chinese medicine (TCM) that has been used to treat Alzheimer's disease (AD). This study was to explore the pharmacological action and molecular mechanism of HPTQC in the treatment of AD. Methods: The possible targets of HTPQC were predicted by the molecular docking technique. Intraperitoneal injection of D-galactose and bilateral injection of Aβ25-35 in hippocampus induced AD rat model. Morris water maze was used to observe learning and memory function. The primary hippocampal neurons were induced by Aβ25-35. Moreover, the apoptosis rate of hippocampal nerve cells was detected through AnnexinV/PI double standard staining. The mRNA and protein levels of GRP78, CHOP, Caspase 12, Caspase 9, and Caspase 3 were detected by PCR and western blot. Results: The prediction results suggest that HPTQC may act on GRP78. HPTQC significantly improved the learning and memory function, and decreased neuronal apoptosis in vivo and in vitro. In addition, HPTQC could decrease the mRNA and protein expression levels of GRP78, CHOP, Caspase12, Caspase9, and Caspase3, and the effect trend was consistent with the specific inhibitor of GRP78. Conclusions: HPTQC has a neuroprotective effect against AD by inhibiting the apoptosis pathway mediated by endoplasmic reticulum stress.